THE PRESERVATION OF THE TAGUS ESTUARY TRADITIONAL BOATS: NEW ISSUES AND CHALLENGES - Fernandes, André; de Sousa, João Figueira; Vicente, Tânia (Journal of Tourism, Sustainability and Well-being, 2018)
Up until the 1960s, Tagus Estuary traditional boats played an important role in the functioning of the economy of the region and city of Lisbon as a transport mode used for the movement of goods between the banks of the Tagus and as support to the movement of cargo to and from the ships anchored in the Port of Lisbon. However, technological progress and development of regional transport system observed afterwards led to functional disuse and gradual decline of these boats. In the 1980s, social and institutional acknowledgement of their cultural and patrimonial value provided for the launch of the process of recuperation and preservation of these traditional boats. However, nowadays the preservation of these patrimonial elements faces a complex of new challenges which in some cases threat their sustainability. Supported by the analysis of the valorisation process of the Tagus Estuary traditional boats and based on experience of various local stakeholders, the article analyses, discusses and systematizes major contemporary challenges for the preservation of these traditional boats.